2022
DOI: 10.3389/fimmu.2022.869365
|View full text |Cite
|
Sign up to set email alerts
|

ILC2s expanded by exogenous IL-33 regulate CD45+CD11b+F4/80high macrophage polarization to alleviate hepatic ischemia-reperfusion injury

Abstract: Hepatic ischemia-reperfusion injury (IRI) is an adverse consequence of hepatectomy or liver transplantation. Recently, immune mechanisms involved in hepatic IRI have attracted increased attention of investigators working in this area. In specific, group 2 innate lymphoid cells (ILC2s), have been strongly implicated in mediating type 2 inflammation. However, their immune mechanisms as involved with hepatic IRI remain unclear. Here, we reported that the population of ILC2s is increased with the development of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These results are supported by recent work demonstrating that ILC2s appear to regulate the polarisation of macrophages to alleviate hepatic IRI after IL-33 administration. 38 Although this study did not investigate the underlying mechanisms, we have demonstrated a critical role for ILC2–IL-13–macrophage pathways in mediating this protection. Moreover, our work suggests that IL-13 may possess an additional protective role in other cells.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…These results are supported by recent work demonstrating that ILC2s appear to regulate the polarisation of macrophages to alleviate hepatic IRI after IL-33 administration. 38 Although this study did not investigate the underlying mechanisms, we have demonstrated a critical role for ILC2–IL-13–macrophage pathways in mediating this protection. Moreover, our work suggests that IL-13 may possess an additional protective role in other cells.…”
Section: Discussionmentioning
confidence: 83%
“…In response to IRI, numerous studies have indeed described how ILC2s become licensed to protect against injury in various organs through suppressing the onset of immune responses or enhancing tissue regeneration. 18 , 22 , 38 , 44 We recently demonstrated for the first time that the ILC2-activating cytokine IL-25, IL-33, or ex vivo -expanded ILC2s could reduce tubular cell injury and improve kidney function in renal IRI. 18 , 22 In the context of hepatic IRI, and consistent with our results, other groups have shown that ILC2s play a protective role by modulating macrophage polarisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 2 innate lymphoid cells stimulated with IL-33 alleviate liver IRI through IL-4-mediated macrophage shifting toward a reparative phenotype that expresses CD11 b + F4/80 high CD206 high in mice ( Zhang et al, 2022 ).…”
Section: Macrophages In Liver Repairmentioning
confidence: 99%